Comparative Analysis of Croatian and Czech Lagging Regions - Marošević, Katarina; Sekur, Tomislav (European Scientific Journal, ESJ, 2018)
Regional development is a central subject of different scientific areas of study, and especially economy since a region in a modern context represents a universal unit of monitoring (regional) development. Independent of the level of their development, national economies mostly bear the burden of regional inequalities and, grosso modo, of the existence of regions that fall behind in development. These regions are most vulnerable in post communist and highly centralized countries such as Croatia and the Czech Republic. Croatia and Czech Republic share many similarities, for example transitional post-communist background with centralized national economies dominated by capital city regions. Considering this, the aim of this paper is to analyse regions in Croatia with respect to their economic and social development with a detailed review of the least developed region. With that in mind, a comparative display of Czech Republic and issues concerning Czech lagging regions in economic aand social development will be used to find the common denominator with similar problems in Croatian regions followed by suggestions for solutions on a regional level. This paper uses methods of description and comparative anaysis, wih an analytical review of data made available by relevant institutions.